2019
DOI: 10.26603/ijspt20190204
|View full text |Cite
|
Sign up to set email alerts
|

Interrater and Test-Retest Reliability of the Y Balance Test in Healthy, Early Adolescent Female Athletes

Abstract: Background: Adolescence is the stage of development marked by peak rates of skeletal growth resulting in impaired dynamic postural control and increased injury risk, especially in female athletes. Reliable tests of dynamic postural control are needed to help identify athletes with balance deficits and assess changes in limb function after injury. Purpose: To estimate the interrater and test-retest (intrarater) reliability of the Y-Balance Test in a group of early adolescent females over a one-month period when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
0
20
1
2
Order By: Relevance
“…The star excursion balance test measures balance in eight directions, whereas the YBT measures it in three directions and has the advantage of being a simple exercise [ 45 ]. Several studies have reported that YBT is useful for measuring dynamic balance and exercise function, not only for athletes but also for elderly individuals, with high validity and reliability [ 46 , 47 ]. When both sides are examined, if there is a difference of over 4 cm in the results, the test is considered abnormal.…”
Section: Discussionmentioning
confidence: 99%
“…The star excursion balance test measures balance in eight directions, whereas the YBT measures it in three directions and has the advantage of being a simple exercise [ 45 ]. Several studies have reported that YBT is useful for measuring dynamic balance and exercise function, not only for athletes but also for elderly individuals, with high validity and reliability [ 46 , 47 ]. When both sides are examined, if there is a difference of over 4 cm in the results, the test is considered abnormal.…”
Section: Discussionmentioning
confidence: 99%
“…Full text eligibility assessment of the remaining 411 articles resulted in 57 articles with 4 in multiple categories (Figure 1). 3,9,[12][13][14] Nine studies 9,25,33,40,46,[51][52][53][54] assessed reliability, 36 studies [12][13][14][23][24][25][26][27][28][29][30]32,35,37,38,[41][42][43][44][45]47,49,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] examined differences in the performance on the YBT-LQ in different populations or reported mean performance on the YBT-LQ in a specific population, and 16 studies 3,3...…”
Section: Study Selectionmentioning
confidence: 99%
“…Nine studies 9,25,33,40,46,[51][52][53][54] assessed reliability of YBT-LQ (see Table 1). Intraclass correlation coefficients (ICCs) for intrarater reliability ranged from 0.57-0.82 in adolescent populations, 40 and 0.85-0.91 in adult populations.…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For adult populations, the YBT-LQ was found to have good-to-excellent inter-rater reliability (ICC 2,1 = 0.80 -1.00) and intra-rater reliability (ICC 3,1 = 0.85-0.91). 11, 26 For adolescents, the within-day inter-rater reliability was reported to be excellent (ICC 2,1 = 0.96 -0.99), 27 whereas the within-day and between-day intra-rater reliability was found only to be fairto-good (ICC 3,1 = 0.57-0.91). [27][28][29] Lastly, for pre-adolescent children, both the within-day (ICC 2,1 > 0.995) and betweenday (ICC 2,1 = 0.91-0.97) inter-rater reliability were excellent.…”
Section: Discussionmentioning
confidence: 99%